Design of bifurcating microchannels with/without loops for cooling of square-shaped electronic components. (5th September 2016) - Farzaneh, Mahsa; Salimpour, Mohammad Reza; Tavakoli, Mohammad Reza
Highlights: Constructal theory was used to design reverting channels for cooling a square piece. Effect of bifurcating loops and their place on cooling performance was studied. The increased number of branches, reduces temperature and pressure drop. Abstract: This study investigates the using of microchannels with/without loops for cooling process of a square electronic component with internal heat generation via convection using the constructal theory. The collection problem of the cooling fluid flowing through the microchannels of a square electronic piece is examined and a solution to overcome this problem is suggested by designing reverting microchannels with/without loops. The proposed microchannel network facilitates the collection of the fluid flowed in radial and bifurcated ducts embedded in the body. This research investigates uniform temperature distribution and maximum temperature reduction to recognize the effect of branching on thermal resistance. The goal is to develop a system configuration that minimizes thermal resistance. The results indicate that increasing the number of branches reduces both temperature and pressure drop. In the test results, the maximum dimensionless temperature is reduced by 10% and 20%, while the maximum dimensionless pressure drop is decreased by 25% and 33% for one and two branch reverting microchannels, in comparison with the case without a branch. Path length ratio, width ratio of channels in each branch of the tree network, and finding the optimal split point are among the parameters investigated in this study.